IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK DALAM PENINGKATAN PROFIL PELAJAR PANCASILA (STUDI DI SMA NEGERI 1 SIKUR) - PUTRI, BAIQ INDAH RISKIA; ZUBAIR, MUH.; BASARIAH, BASARIAH; MUSTARI, MOHAMAD (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
The Driving School Program is one of the efforts to realize the vision of Indonesian Education in realizing an advanced Indonesia that is sovereign, independent and has personality through the creation of Pancasila Students. The Driving School Program focuses on developing holistic student learning outcomes which include competency (literacy and numeracy) and character, starting with superior human resources (school principals and teachers). The aim of this study is to explain the implementation of the driving school program in strengthening the profile of Pancasila students and the supporting and inhibiting factors. This research uses a qualitative approach with a case study method. Data collection techniques use observation, interviews and documentation. The results obtained from the data include, among others. (1) the form of implementation of the Driving School program is through consultative and asymmetric mentoring interventions, data-based planning, new paradigm learning, strengthening school human resources, and school digitalization; (2) developing the profile of Pancasila students through the driving school program implemented through intracurricular, extracurricular and positive cultural activities, and (3) supporting factors in implementing the driving school program, namely full support by the school in carrying out various activities of the driving school program which is a support in the success of the program and the quality of human resources as well as collaboration between educational and educational staff. Meanwhile, the inhibiting factors are students who are heterogeneous, which becomes an obstacle in character formation and teaching staff who are still unable to switch from the old curriculum. ABSTRAKProgram Sekolah Penggerak merupakan salah satu upaya dalam mewujudkan visi Pendidikan Indonesia yaitu Indonesia maju yang berdaulat, mandiri, dan berkepribadian dengan terciptanya Pelajar Pancasila. Program Sekolah Penggerak berfokus pada pengembangan hasil belajar siswa secara holistik yang mencakup kompetensi (literasi dan numerasi) dan karakter, diawali dengan SDM yang unggul (kepala sekolah dan guru). Penelitian ini bertujuan untuk menjelaskan implementasi program sekolah penggerak dalam penguatan profil pelajar pancasila dan faktor pendukung serta penghambatnya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil yang diperoleh dari data, antara lain. (1) bentuk implementasi program Sekolah Penggerak adalah melalui intervensi pendampingan konsultatif dan asimetris, perencanaan berbasis data, pembelajaran paradigma baru, penguatan SDM sekolah, dan digitalisasi sekolah; (2) pengembangan profil pelajar pancasila melalui program sekolah penggerak dilaksanakan melalui kegiatan intrakurikuler, ektrakurikuler dan budaya positif, dan (3) faktor pendukung dari pelaksanaan program sekolah penggerak yaitu dukungan penuh oleh sekolah dalam melaksanakan berbagai kegiatan program sekolah penggerak yang merupakan penunjamg dalam keberhasilam program dan kualitas SDM serta kolabirasi antara tenaga pendidk dan kependidikan. Sedangkan faktor penghambatnya yaitu siswa yang heterogen sehingga menjadi kendala dalam pembentukan karakter dan tenaga pendidik yang masih belum bisa beralih dari Kurikulum lama.